A placebo‐controlled pilot study of a wearable morning bright light treatment for probable PTSD. Issue 7 (17th April 2019) - Zalta, Alyson K.; Bravo, Karyna; Valdespino‐Hayden, Zerbrina; Pollack, Mark H.; Burgess, Helen J.
Abstract: Background: Evidence‐based treatments for post‐traumatic stress disorder (PTSD) have poor uptake and remission rates, suggesting that alternative treatments are needed. Morning bright light may be an effective treatment for PTSD given its established effects on mood and sleep, however, there are no published trials. Methods: We conducted a placebo‐controlled pilot trial of a wearable light device, the Re‐timer®, for individuals with probable PTSD. Individuals were randomly assigned to the active Re‐timer® ( n = 9) or a placebo Re‐timer® dimmed with neutral density filters ( n = 6). Participants self‐administered the treatment at home 1 hr each morning over 4 weeks. PTSD and depression symptoms were assessed at pre‐ and post‐treatment. Results: The Re‐timer® was well tolerated and the perceived benefit was high, though treatment adherence was only moderate. Those in the active group were more likely to achieve a minimal clinically important change in PTSD and depression symptoms and had larger symptom reductions than those in the placebo group Conclusions: A wearable morning light treatment was acceptable and feasible for patients with probable PTSD. This study provides initial proof‐of‐concept that light treatment can improve PTSD. A larger trial is warranted to establish treatment efficacy. NCT#: 03513848